Day 1 Tue, September 30, 2014 2014
DOI: 10.2118/171618-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Fracturing: A Marcellus Case Study of an Engineered Staging Completion Based on Rock Properties

Abstract: In multi-fractured horizontal wells, the wellbore is segmented into stages that are stimulated separately. This segmentation is traditionally geometrically based on a specific stage length ("geometric staging"); which is usually determined by trial and error including cost and production history considerations. However, this approach does not take geological and geomechanical properties into account. An alternative method for staging ("engineered staging") uses these properties to determine the wellbore segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Slocombe et al (2013) do not, however, report the impact on productivity of the wells. On the other hand, Lim et al (2014) report production impacts relative to a control group for 4 wells in the Marcellus Shale. The log-driven placement cases produced over 20% more gas over their first 400 days than the control group.…”
Section: Modeling Insightsmentioning
confidence: 99%
“…Slocombe et al (2013) do not, however, report the impact on productivity of the wells. On the other hand, Lim et al (2014) report production impacts relative to a control group for 4 wells in the Marcellus Shale. The log-driven placement cases produced over 20% more gas over their first 400 days than the control group.…”
Section: Modeling Insightsmentioning
confidence: 99%
“…Therefore, the effect of stress shadow should be weakened, or the increased resistance caused by stress shadow should be balanced, to promote a uniform flow distribution between fractures. Quite a few technologies have been proposed to promote uniform fracture propagation, such as limited-entry fracturing, temporary plugging fracturing, and fracture optimization [19][20][21]. Wu et al [22] investigated multi-fracture propagation and found that reducing the perforation number and adjusting non-uniform cluster spacing could effectively improve the unevenness of the fracture propagation using the displacement discontinuity method (DDM).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the low porosity and permeability of shale gas reservoirs, hydraulic fracturing is regarded as a prominent technology for industrial gas production [1]. It has been proven by practice that multi-cluster fracturing of horizontal wells is the key technology for the successful development of shale gas reservoirs [2,3]. In the multi-cluster fracturing of a horizontal well, the fracturing fluid is pumped into the horizontal wellbore at high speed.…”
Section: Introductionmentioning
confidence: 99%